Investigating knowledge, attitudes and beliefs of undergraduate students towards Herpes Simplex Virus-2 and diagnosis of this infection - Shange, Ntokozo Thamsanqa; Jaya, Ziningi; Pillay, Roxanne (Student's Journal of Health Research Africa, 2025)
Introduction Herpes simplex virus type 2 (HSV-2) is among the most prevalent sexually transmitted viral infections globally, with an estimated 536 million infections reported among individuals aged 15–49 years. Despite its widespread occurrence, awareness and understanding of HSV-2 remain limited in many populations. The aim of this study was to investigate the knowledge, attitudes, and beliefs of undergraduate students at a University of Technology (UoT) regarding HSV-2 and HSV-2 testing. Methodology A prospective, cross-sectional study design was employed to assess variables related to knowledge, attitudes, and beliefs. The study population included undergraduate students at all levels of study at a UoT in Durban, KwaZulu Natal, South Africa. Data were collected via structured surveys and analysed using Microsoft Excel to generate descriptive statistics. Results A total of 139 undergraduate students participated in the study, with females comprising 53.2% (n = 74) and males 46.8% (n = 65). Participants’ ages ranged from 18 to 24 years, with a mean age of 25 years. Findings revealed that accurate knowledge of HSV-2 was generally limited; only 47.5% of respondents reported awareness of HSV-2 infection, transmission, and symptoms. Attitudes and beliefs about HSV-2 testing were also varied, with many students demonstrating uncertainty regarding the importance of testing. Conclusion The study highlights a substantial gap in knowledge regarding HSV-2 among undergraduate students. These findings highlight the need for targeted sexual health education programs and awareness campaigns to improve understanding of HSV-2 transmission, symptoms, and testing, which could contribute to better prevention and early detection practices among young adults.